Multifunctional Landscapes (MFL) shaping sustainable future - Wandera, O.; Masso, C.; Flintan, Fiona E.; Desta, L; Ghinassi, C. (International Livestock Research Institute, 2025)
The video shows how landscape multifunctionality contribute to integrating the three Rio Conventions (i.e., Convention on Biological Diversity, United Nations Convention to Combat Desertification, and United Nations Framework Convention for Climate Change) to sustainably transform food, land, and water systems in a climate crisis